2007
DOI: 10.1097/mcp.0b013e328012e053
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic lung volume reduction: indications, effects and prospects

Abstract: A number of case series have been published which show promise and the results of a large multicentre randomized controlled study are anticipated in 2007. A number of other bronchoscopic treatments for emphysema are also under development, including airway bypass techniques and tissue glues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…However, practice has shown that a clinically significant volume reduction is not always achieved, with atelectasis obtained in about 50% of cases [12,13,14,15]. Observations suggest that the lack of volume reduction is due to collateral ventilation [16,17], a phenomenon with major implications for patient selection and EBV treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, practice has shown that a clinically significant volume reduction is not always achieved, with atelectasis obtained in about 50% of cases [12,13,14,15]. Observations suggest that the lack of volume reduction is due to collateral ventilation [16,17], a phenomenon with major implications for patient selection and EBV treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Collateral ventilation has been linked to interlobar fissure incompleteness [15,16,17,18,19]. The existence of intact, incomplete, or absent interlobar fissures [defined by visual inspection of computed tomography (CT) scans] [20] has been extensively described in the literature [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopic approaches to achieve lung volume reduction have recently been explored as safer alternatives to lung volume reduction surgery (LVRS) for treating advanced emphysema [1,2]. While these techniques are associated with less morbidity and mortality than LVRS, the majority have demonstrated limited effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy exists over the unilateral or bilateral surgery in one stage or multiple sessions. However, studies indicate that long-term effects of one-side LVRS are similar to that of both sides [7,8].…”
Section: Discussionmentioning
confidence: 99%